LEGAL PROTECTION FOR DOCTORS AND LEGAL CONSEQUENCES FOR PATIENTS WHO LIE ABOUT MEDICAL STATUS IN THE TIME OF THE COVID-19 PANDEMIC - Nugroho Nugroho; Azis Budianto; Evita Isretno Israhadi (Proceeding International Conference Of Innovation Science, Technology, Education, Children And Health, 2021)
The Covid-19 pandemic has caused deep sorrow for the world community and Indonesian people. In fighting the Covid-19 pandemic, doctors are a profession at the forefront. But in fact, many patients lie about their medical status which is an obstacle to eradicating the Covid-19 pandemic. This study aims to determine how the legal protection of doctors and what are the legal consequences of patients who lie about their medical status. The research method used in this research is normative legal research and empirical law. The results of the study explain that the health worker profession really needs to get legal protection in carrying out its duties, as well as the right to occupational safety and health in providing health services and the legal consequences for patients who lie have been described in article 14 paragraph (1) of Law of the Republic of Indonesia Number 4 1984 regarding the outbreak of infectious diseases.